2006
DOI: 10.1099/ijs.0.64251-0
|View full text |Cite
|
Sign up to set email alerts
|

‘Candidatus Phytoplasma americanum’, a phytoplasma associated with a potato purple top wilt disease complex

Abstract: Potato purple top wilt (PPT) is a devastating disease that occurs in various regions of North America and Mexico. At least three distinct phytoplasma strains belonging to three different phytoplasma groups (16SrI, 16SrII and 16SrVI) have been associated with this disease. A new disease with symptoms similar to PPT was recently observed in Texas and Nebraska, USA. Two distinct phytoplasma strain clusters were identified. One belongs to the 16SrI phytoplasma group, subgroup A, and the other is a novel phytoplasm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
33
0
4

Year Published

2007
2007
2020
2020

Publication Types

Select...
4
4
2

Relationship

0
10

Authors

Journals

citations
Cited by 88 publications
(37 citation statements)
references
References 14 publications
0
33
0
4
Order By: Relevance
“…Most of these studies are based on investigation of sponge – associated endosymbiotic microorganisms, while the information about microbes internally or externally associated with other animals is limited (but, see: Bodammer and Sawyer, 1981; Pukall et al, 2001; Harder et al, 2003; Kittelmann and Harder, 2005; Perez-Matos et al, 2007; Winters et al, 2010). It has been demonstrated that the community composition of epibiotic bacteria associated with the same sponge species from different locations remained consistent (Lee et al, 2006a, 2011), while microbial communities associated with different species of sponges differed substantially (Qian et al, 2006; Lee et al, 2011). This suggests a certain host-specificity of the biofilms (as it has been shown in algae) while in the vast majority of cases a mandatory restriction of a given bacterial strain to a particular host species has not yet been shown.…”
Section: Bacterial Communities At the Surface Of Macroorganismsmentioning
confidence: 99%
“…Most of these studies are based on investigation of sponge – associated endosymbiotic microorganisms, while the information about microbes internally or externally associated with other animals is limited (but, see: Bodammer and Sawyer, 1981; Pukall et al, 2001; Harder et al, 2003; Kittelmann and Harder, 2005; Perez-Matos et al, 2007; Winters et al, 2010). It has been demonstrated that the community composition of epibiotic bacteria associated with the same sponge species from different locations remained consistent (Lee et al, 2006a, 2011), while microbial communities associated with different species of sponges differed substantially (Qian et al, 2006; Lee et al, 2011). This suggests a certain host-specificity of the biofilms (as it has been shown in algae) while in the vast majority of cases a mandatory restriction of a given bacterial strain to a particular host species has not yet been shown.…”
Section: Bacterial Communities At the Surface Of Macroorganismsmentioning
confidence: 99%
“…Advantageously, the RFLP analysis-based scheme also distinguishes subtle pattern differences, making it possible to differentiate distinct subgroups within a phytoplasma group. Following inception of the scheme, 19 groups and more than 40 subgroups were delineated through conventional RFLP analysis (Lee et al 2006;Al-Saady et al 2008).…”
Section: Gene-based Classificationmentioning
confidence: 99%
“…Comparative cladistic analyses were performed by using rplV-rpsC and 16S rRNA gene sequences from phytoplasma strains across 12 distinct phytoplasma 16Sr groups (Lee et al, 1998(Lee et al, , 2006b), other representative mollicutes and Grampositive walled bacteria. The analyses resulted in 32 equally parsimonious trees based on rp genes and 126 trees based on the 16S rRNA gene; representative trees were selected (Fig.…”
Section: Congruence Between the Rp Gene-based Phylogenetic Tree And Tmentioning
confidence: 99%